Analiza formalna i semantyczna przymiotników od toponimicznych w języku rosyjskim, polskim i macedońskim (na materiale słownikowym) - Stryszewska, Maria (2023)
The subject of this article is a formal and semantic analysis of adjectives derived from toponyms (or names of inhabitants) in Russian, Polish and Macedonian. The common feature of this type of derivation in all three languages is the fact that they are combined almost exclusively with the formative -ский/-ski/-ски and its compound variants. I take into account the morphological and semantic characteristics of the word-formation base, its origin and morphological alternations within derivatives. I focus on the semantic characteristics of toponymic adjectives in the discussed languages. These types of derivatives are relational adjectives, and thus their specific meaning can only be clarified in the noun context.
Keywords: relational adjectives; Slavic word formation; confrontational word formation; toponyms